2016
DOI: 10.1097/spv.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Obesity on Intraoperative Complications and Prolapse Recurrence After Minimally Invasive Sacrocolpopexy

Abstract: In women undergoing minimally invasive sacrocolpopexy, obesity is associated with increased blood loss, longer operative times, and more intraoperative complications, specifically conversions to laparotomy. Even after correcting for blood loss, surgeon experience, and concomitant hysterectomy, obese women were 3 times as likely to have an intraoperative complication. Our data did not show that obesity was associated with increased risk of prolapse recurrence; however, postoperative follow-up was limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This study builds on previous studies comparing short-term outcomes after sacrocolpopexy and vaginal surgery between normal weight, overweight, and obese patients by assembling a cohort of overweight and obese patients that is much larger than the largest cohort represented in these single-center retrospective studies. [12][13][14][15][16]20 In addition, we expanded on the analysis of women of all BMI classes by Linder et al 11 by constructing a robust prespecified multivariable model adjusting for more preoperative comorbidities to isolate the contribution of BMI to the odds of complication by surgical approach in the setting of the known increased chronic disease burden in this population. 30 Strengths of this study include that the cohort represents a North America-wide, population-based sample comprising both tertiary and community sites derived from a validated source with an established mechanism to minimize loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study builds on previous studies comparing short-term outcomes after sacrocolpopexy and vaginal surgery between normal weight, overweight, and obese patients by assembling a cohort of overweight and obese patients that is much larger than the largest cohort represented in these single-center retrospective studies. [12][13][14][15][16]20 In addition, we expanded on the analysis of women of all BMI classes by Linder et al 11 by constructing a robust prespecified multivariable model adjusting for more preoperative comorbidities to isolate the contribution of BMI to the odds of complication by surgical approach in the setting of the known increased chronic disease burden in this population. 30 Strengths of this study include that the cohort represents a North America-wide, population-based sample comprising both tertiary and community sites derived from a validated source with an established mechanism to minimize loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of apical repair surgical approaches have been completed in a population of patients across all body mass index (BMI) categories and no difference was found in short-term outcomes between approaches. 10,11 Several studies have compared outcomes following vaginal surgery 12,13 and sacrocolpopexy [14][15][16][17][18][19][20] between obese and nonobese patients noting higher complication rates in obese patients. In addition, several systematic reviews have examined complications between approaches, but these have not compared approaches in patients with elevated BMI.…”
mentioning
confidence: 99%
“…A study by Turner et al evaluated complication rates and outcomes in normal weight, overweight and obese women undergoing both robotic sacrocolpopexy (RSC) and LSC reported that obese women were more likely to undergo RSC ( p = 0.004 ) [13]. They found increased blood loss in obese women ( p = 0.003 ), although total blood loss was not clinically significant, at <100 ml, for all groups, which is in keeping with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were divided according to preoperative BMI into two groups, i.e., nonobese (BMI <30) and obese (BMI ≥30). [ 15 ] The inclusion criteria for this study were LSC with concomitant supracervical hysterectomy (SCH) or UP for preoperative POP-Q stage II or higher. The general stage of POP was defined as the most severe stage in one or more of the anterior, apical, and posterior vaginal compartments.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%